Fecaloma causing small bowel obstruction in the absence of risk factors: a case report - Youssef Ahmad; Umer Siddiqui; Ayman Ahmed; Aiswarya Sudheer; Tejaswi Chetla; Inayat Shergill; Fadi Souleiman (Journal of Medical Case Reports)
Abstract Background Small bowel obstruction is a common surgical emergency typically caused by adhesions, hernias, and malignancies. However, ileal fecalomas represent an exceptionally rare etiology, with few cases reported in literature. This case study and literature review aim to highlight an unusual cause of small bowel obstruction, emphasizing the diagnostic challenges and management strategies. Case presentation A 60-year-old Middle Eastern female patient from Syria with a 1-year history of chronic constipation presented with abdominal pain, vomiting, and an inability to pass feces. Diagnostic imaging confirmed small bowel obstruction, which was caused by a fecal mass proximal to the ileocecal junction. Surgical extraction successfully resolved the obstruction. Conclusion This case underscores the importance of considering fecal impaction as a differential diagnosis in patients with chronic constipation and highlights the effectiveness of surgical intervention in resolving such obstructions. A comprehensive review of literature on unusual causes of small bowel obstruction, including imaging characteristics and management approaches, is also provided to enhance clinical awareness and improve patient outcomes.